Pulmonary cytopathology - Erozan, Yener S.; Ramzy, Ibrahim (Essentials in Cytopathology, 2014)
The Essentials in Cytopathology book series fulfills the need for an easy-to-use and authoritative synopsis of site specific topics in cytopathology. These guide books fit into the lab coat pocket and are ideal for portability and quick reference. Each volume is heavily illustrated with a full color art program, while the text follows a user-friendly outline format. This new edition of Pulmonary Cytopathology is fully updated and expanded providing more detailed discussion of the role of new techniques such as EUS needle biopsy and specific issues of adequacy assessment. The section on subclassification of poorly-differentiated non-small cell carcinomas has been expanded to include accuracy of diagnosis in small samples, the new classification of adenocarcinoma and NSCC, currently-used ancillary techniques; i.e., immunohistochemistry, molecular/genetic techniques and therapeutic applications. Molecular techniques have been added as needed for targeted therapy. The text and illustrations have been expanded throughout.